(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article describes the life and works of Gafur Ghulam, one of the brightest representatives of Uzbek literature, and the themes of patriotism, love, youth, as well as legal issues, which are sung in them.